Meeting report: Consensus recommendations for a research agenda to address immunosuppressant nonadherence in organ transplantation. Issue 9 (18th August 2018) - Maldonado, Angela Q.; West‐Thielke, Patricia; Dew, Mary Amanda; Peipert, John Devin; Heldenbrand, Seth; Kaiser, Tiffany E.; Chisholm‐Burns, Marie; Potter, Lisa M.; ,
Abstract: Despite advances in the field of transplantation, immunosuppressant medication nonadherence (NA) remains a primary contributor to suboptimal long‐term outcomes. Due to the multidimensional and multifactorial causes of medication NA, studies to date have focused on individual differing facets or single point barriers of NA with relative success. However, these successes have not proven to be sustainable, partly due to the intense resources needed for continued viability. This article provides a summary of a 2‐day meeting held in April 2017 (Chicago, IL) prior to the American Transplant Congress in which a multidisciplinary group convened to identify the unmet research needs related to medication NA in transplantation. Thought leaders in the field presented the past, present, and future directions of medication NA with the primary outcome of designing, developing, and ranking targeted interventions into a dynamic research agenda to identify which interventions maintained effects over time. Break‐out sessions were created based on the five World Health Organization (WHO) dimensions of adherence. Participants were then organized into the newly formed AST Transplant Pharmacy Adherence Consortium (AST TPAC) research group. This meeting report summarizes the content of the symposium, and the development, background, and future directions of the AST TPAC.